Identificação de regiões cromossômicas e genes envolvidos na craniossinostose - Faria, Ágatha Cristhina de Oliveira (2014)
Craniosynostosis is the second most common developmental anomaly. It consists in a premature fusion of the skull sutures or more as a result of the differentiation and proliferation of cells from calvaria bone triggered by abnormal activation of cell signaling pathways during embryogenesis. Syndromic forms account for 30% of cases, of which 30% are explained by mutations in one of the eight described genes (FGFR1, FGFR2, FGFR3, TWIST1, EFNB1, IN, MSX2, and RAB-23) and 20% are due to deletions, duplications or other microscopic structural changes. Another important cause of this type of craniosynostosis are submicroscopic structural changes, which can only be identified by molecular techniques, especially by Comparative Genomic Hybridization-based Array (aCGH). The aCGH is a high resolution technique for identifying genomic regions and changes or CNVs related to specific phenotypes, besides enabling the characterization of breakpoints and lead to the identification of candidate genes. Aiming to identify new chromosomal regions and genes involved in craniosynostosis aCGH was performed in five patients with craniosynostosis associated with other congenital anomalies without definitive diagnosis, two with scaphocephaly, two with trigonocephaly and one with both. Four deletions were identified in regions 10q26.12-q26.3, 1q21.1, 10q11.22 and 2p25.1- p24.1 and 15q13.3 duplication in the region, which ranged from 0.4 to 12.9 Mb Mb. The candidate genes for craniosynostosis in 10q26.12-q26.3 were FGFR2, PTPRE , DOCK, VENTX, NKX-2.1, HMX2 and HMX3; in 1q21.1 HYDIN2, PDE4DIP, PIAS3 and HFE2; in 10q11.22 GDF10 and GDF2; and from 2p25.1-p24.1 MYCN, E2F6 and SMC6. Only CHRNA7 is present in 15q13.3. There is controversy over phenotypic consequences of CNVs in this regionfor this reason we cannot consider it a good candidate. Besides contributing to the diagnosis of the patients, the use of aCGH allowed the identification of potential genomic regions and genes involved in two different types of craniosynostosis. The main significance of this work is that these genes are likely to explain the craniosynostosis in other patients.